ENGLISH CONTENT CREATOR TRAINING FOR TOUR GUIDES AT KEBUMEN ENGLISH TOURISM VILLAGE (KWIK) AS A MEANS TO OVERCOME ANXIETY IN GUIDING TOURS IN ENGLISH - Nugraha, Novanda Alim Setya; Chaeruman, Uwes Anis; Lustyantie, Ninuk (Esteem Journal of English Education Study Programme, 2025)
Anxiety is one of the affective factors that influences foreign language learning, particularly in speaking. Anxiety appears to be an important factor in language learning progress, as it has a hindering effect on learners' oral performance. One approach to addressing this issue is through "English Content Creator" training. This training aims not only to improve English language skills but also to equip tour guides with the ability to create creative content relevant to tourism. This research employs a qualitative descriptive method with a literature review approach. As we know, typical English learners among tour guides in these villages often experience high levels of apprehension when speaking, such as fear of making mistakes, nervousness, and lack of confidence. To help them overcome this anxiety, it is crucial for educators to encourage tour guides to learn English in a fun and engaging way, one of which is through the use of content creators.